Evaluation of the Physical Quality of Fermentation of Rice Bran with Different Levels of Effective Microorganisms (EM4) - Ririn Angriani; Anggi Derma Tungga Dewi (Journal of Tropical Animal Science and Technology, 2026)
This study aimed to evaluate the effect of rice bran fermentation using Effective Microorganisms (EM4) on its physical quality as a livestock feed ingredient. The experiment was arranged in a Completely Randomized Design (CRD) with five EM4 levels, namely 0%, 5%, 10%, 15%, and 20%, each with three replications. The fermentation process was carried out for 21 days with the addition of 1% sugar as a nutrient source for microorganisms, and the rice bran was stored in airtight plastic bags. The observed parameters included organoleptic characteristics (color, aroma, texture, clumping ability, and insect presence), pH value, and bulk density. Data were analyzed using analysis of variance (ANOVA) at a significance level of P<0.05, followed by a post hoc test when significant differences were detected. The results showed that EM4 supplementation had a significant effect on the organoleptic quality of rice bran (P<0.05), but had no significant effect on pH value and bulk density (P>0.05). Fermentation of rice bran using EM4 at levels of 5–10% produced the best physical quality, characterized by yellowish-brown to brown color, moderate texture, moderate aroma, moderate to crumbly clumping ability, and relatively low insect presence. Therefore, the use of EM4 at moderate levels has the potential to improve the physical quality and stability of rice bran as a livestock feed ingredient.